FAKTOR - FAKTOR YANG MEMPENGARUHI SIMPANAN MUDHARABAH PADA BANK SYARIAH DI INDONESIA - Arye Nursa Asyik, 12.05.52.0183; Puspitasari, Elen (Students Journal of Accounting and Banking, 2016)
Mudharabah deposits are deposits which is based on a kind of partnership agreements. There are two parties involved in the mudharabah deposits, where the first party as shahibul maal can be referred to customers who provide the funds and the second party as mudharib be called Islamic banks are responsible for the management. The purpose of this study was to identify factors that influence the Mudharabah deposits in Islamic banks in Indonesia. Objects that are used as research are factors thought to influence the Mudharabah deposits in Islamic banks during the period 2012-2014, in the form of benchmark interest rate, the rate of profit sharing, inflation, financing to deposit ratio, the size of the Bank, non-performing financing and promotion costs , Population and samples taken consisted of Islamic Banks and Sharia Business Unit by taking the data derived from the entire financial performance of Islamic banks in Indonesia in the period 2012 to 2014, obtained a total sample of 101 data obtained by purposive sampling technique. Hypothesis testing using multiple regression analysis. The results showed that the benchmark interest rate, and inflation does not affect the mudhrabah deposits in Islamic banks in Indonesia. Variable Financing to Deposit Ratio, the size of the bank, and the cost of the promotion of significant positive effect on mudhrabah deposits in Islamic banks in Indonesia. Non Performing Financing significant negative effect on mudhrabah deposits in Islamic banks in Indonesia. Determination coefficient of 0.783 indicates that the independent variable on the dependent variable mudaraba deposits amounted to 78.3% and the remaining 21.7% is influenced by other variables not included in this study.Keywords: Islamic Banking, The Benchmark Interest Rate, Profit Sharing, Financing To Deposit Ratio, Inflation, Bank Size, Non Performing Financing, Promotion Costs, Mudharabah Deposits